Toy manufacturing as part of management education - Balashova, Maria; Pavlovskaya, Irina (Proceedings of the 2014 IEEE NW Russia Young Researchers in Electrical and Electronic Engineering Conference : 3-5 February 2014, 2014)
Business game as an imitating active learning method was first applied in a practical management sphere, but now more and more widely used in higher education field. In order to involve students in the learning process and consider in a practical example some theoretical issues, studied by students in various disciplines earlier, we developed a business game "Production process". The essence of the game is to organize a real process of paper airplanes production by students and improve this process by using quality management methods and tools. The article gives a description of the business game "Production process" (its goals and objectives, the sequence of its implementation and its interaction with a process of quality management studying). In the article conclusion there are descriptions of several ways of further development of our business game.